Design - Wiener, Barbara (Minnesota : Learning Zone Express, 2001)
This fast-moving, stimulating video explores the elements of design - line, shape, pattern, texture, and color - in the usual design disciplines; interior, clothing, landscape, and architecture, as well as through more unusual venues; professional models on the catwalk, a nursery school, and even the family dog.
vol.1 The elements of design - vol.2 The principles ofdesign
Writer, Laura Gross ; director of photography, William Hommeyer